Utilization of Information and Communication Technology as Arabic Learning Media - Faizal Pikri (HK-Publishing, 2022)
AbstractThe problem of learning Arabic in various educational institutions, the teaching staff allows for the modification of teaching and learning methods. Understanding expressions and grammar is also a challenge for students because they cannot master the language in a short period of time and find what is spoken to be very boring. This can be accomplished through the advancement of technology, which contains a wealth of information that can be used to improve learning outcomes. The purpose of this study is to discuss the role of technology in the alignment and sustainability of Arabic learning, as well as whether information and communication technology as a learning medium can increase students' interest in learning Arabic. The qualitative descriptive method is used in this paper to answer some of the questions raised above. The study's findings indicate that learning media plays a critical role in increasing students' motivation to learn in order to avoid boredom. Through the internet, interactive CDs, and Arabic E-Learning Programs, information and communication technology can be used as a learning medium.Keywords: Information and Communication Technology, Learning, Arabic. AbstrakMasalah pembelajaran bahasa Arab di berbagai lembaga pendidikan, tenaga pengajar memungkinkan adanya modifikasi metode belajar mengajar. Memahami ekspresi dan tata bahasa juga merupakan tantangan bagi siswa karena mereka tidak dapat menguasai bahasa dalam waktu singkat dan menganggap apa yang diucapkan sangat membosankan. Hal ini dapat dicapai melalui kemajuan teknologi yang mengandung banyak informasi yang dapat digunakan untuk meningkatkan hasil belajar. Tujuan dari penelitian ini adalah untuk membahas peran teknologi dalam penyelarasan dan keberlanjutan pembelajaran bahasa Arab, serta apakah teknologi informasi dan komunikasi sebagai media pembelajaran dapat meningkatkan minat belajar bahasa Arab siswa. Metode deskriptif kualitatif digunakan dalam makalah ini untuk menjawab beberapa pertanyaan yang diajukan di atas. Hasil penelitian menunjukkan bahwa media pembelajaran berperan penting dalam meningkatkan motivasi belajar siswa agar tidak terjadi kebosanan. Melalui internet, CD interaktif, dan Program E-Learning Bahasa Arab, teknologi informasi dan komunikasi dapat digunakan sebagai media pembelajaran.Kata kunci: Teknologi Informasi dan Komunikasi, Pembelajaran, Bahasa Arab.